Molecular mechanisms for reprogramming hippocampal development and function by early-life stress - Mathias V. Schmidt (Frontiers Research Topics, 2016)
The early postnatal period is a crucial stage for hippocampal development. During this critical period, the neonatal hippocampus is highly sensitive to the detrimental consequences of adverse environmental factors. Extensive clinical and preclinical evidence has shown that traumatic events early in life have profound and persistent effects on hippocampal function and behavior. This research topic focuses on the acute and lasting effects of early-life stress on various developmental processes in the hippocampus, and aims to uncover the molecules that are responsible for early-life stress-programmed effects and underlie resilience or vulnerability to stress-related neuropsychiatric disorders later in life. We hope the articles in this research topic will provide novel insights and stimulate future studies on the mechanisms of early-life stress and brain development.